2022
DOI: 10.3389/fpsyg.2022.866361
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analyzing the Impact of the Internet of Things-Based Industry 4.0 on Circular Economy Practices for Sustainable Development: Evidence From the Food Processing Industry of China

Abstract: The Industry 4.0 concept proposes that new cutting-edge technologies, such as the Internet of Things (IoT), will grow. The acceptance of IoT in the circular economy (CE) is still in its infancy, despite its enormous potential. In the face of growing environmental affairs, IoT based Industry 4.0 technologies are altering CE practices and existing business models, according to the World Economic Forum. This research investigates the function of IoT-based Industry 4.0 in circular CE practices, as well as their im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 95 publications
(90 reference statements)
0
10
0
1
Order By: Relevance
“…The studies and discussions on the use of I4 in the food sectors in particular have been reported in the literature [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies and discussions on the use of I4 in the food sectors in particular have been reported in the literature [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ,…”
Section: Resultsmentioning
confidence: 99%
“…There have been increasing numbers of countries employing I4 in their food agricultural activities to cost-effectively supply the increasing demand for food among their increasing population sizes ( Figure 8 a). The following papers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This perspective opens the door to a potential discussion regarding the application of foreign solutions in domestic electromobility development programs, such as incentives or energy infrastructure modernization [47] and national strategies [48,49]. On the other hand, potential drivers of electric vehicles are concerned about the lack of charging stations [50,51], while facilities owners, where stations would be useful, are hesitant to build because of the low number of electric cars [52]. Although there are multiple challenges related to very specific solutions related to the availability of electricity production from different sources or to the energy storage for charging stations, they are not subject of this research.…”
Section: Introductionmentioning
confidence: 99%